The Mystery Of The Strange Messages - Blyton, Enid (London Egmont, 2013)
Someone is sending him nasty messages. There is only one place he can turn for help - the Find-Outers, now including Ern!
Keywords: Children's Literature - Fiction : Detective / Mystery